Geological impact on the course of the Great Zab River between (Rizan and its estuary) using geometric Indicators - kawaKawa Jabar Rahman; Tahseen Abdularaman Azeez (Zanco Journal of Humanity Sciences)
The study has conducted on a part of the Great River between (Rezan and its mouth) with the aim of determining the effect of geological factors on the stream of the Great River, based on the indicators and equations of morphometry such as identifying areas that have been affected by tectonic activity to some extent on the river stream, by using the (SL Index) on the parts of the river stream based on the determination of elevation points through Digital Elevation Model data (Dem 12.5m) by selecting (29 elevation points) on the entire stream. Then determine the length of each part based on the (Arc map 10.0) program. At the same time, using indicators of the relative relationship between the width of the river valley base to the height (Vf) and the value of symmetry and asymmetry of the river bends in the area.